Prevalence of ABO-Rh positive blood groups in relation to hypertension and type 2 diabetes mellitus among the male urban population of Deoghar, Jharkhand: a cross sectional study - Gogoi, Heemanshu Shekhar; Shankar, Om; Dhenwal, Mukul (International Journal of Research in Medical Sciences, 2021)
Background: Hypertension is the subsequent elevation of the systemic arterial pressure to a level that places the patients at increased risk for target organ damage. Type 2 diabetes mellitus is characterised by the common phenotype of hyperglycemia due to genetic and metabolic defects in insulin action and/or secretion. Methods: This study was performed to evaluate the prevalence of ABO-Rh positive blood groups among the male hypertensive and type 2 diabetic urban population of Deoghar. It was a cross-sectional population based study. 356 hypertensive and 425 type 2 diabetic male subjects were selected based on inclusion and exclusion criteria. Their basal blood pressures were determined using palpatory and auscultatory method. The random blood glucose levels of the subjects were estimated and their blood groups were also determined using slide haemagglutination technique. Results: Among the hypertensive subjects ‘O’ Rh positive was the most prevalent (41%), followed by ‘B’ Rh positive (34%), ‘A’ Rh positive (17%) and lastly ‘AB’ Rh positive blood group (8%). Again, among the type 2 diabetic subjects ‘B’ Rh positive was most prevalent (45%), followed by ‘O’ Rh positive (36%), ‘A’ Rh positive (12%) and finally ‘AB’ Rh positive blood group (7%). Conclusions: This study concludes that ‘B’ Rh positive and ‘O’ Rh positive blood groups are more prevalent as compared to other ABO-Rh positive blood groups among the male hypertensive and type 2 diabetic urban population of Deoghar. Thus, the persons belonging to these two blood groups should take adequate precautions since their childhood against these co-morbidities as they are more prone to develop them.